Indo-Slang and Identity Performance: The Sociolinguistics of 'Bahasa Anak Jaksel' as a Marker of Neoliberal Class Distinction - Firdhaus, Muhammad; Rajagukguk, Elia Binsar; Gaol, Tiara Boru Lumban (Indonesia Discourse, 2025)
The linguistic phenomenon popularly known as Bahasa Anak Jaksel (South Jakarta slang)—characterized by frequent code-switching between Indonesian and English—has evolved into a significant cultural signifier in contemporary Indonesia. This paper examines the sociolinguistic functions of this hybrid language through the lens of Pierre Bourdieu’s "cultural capital." By analyzing social media content and conducting focus group discussions among urban youth, the study explores how linguistic hybridization serves as a tool for identity performance and class distinction. The research finds that while the slang is often ridiculed as a sign of superficiality, it functions as a strategic marker of neocolonial cosmopolitanism, signaling the speaker’s access to international education and global neoliberal networks. Furthermore, the discourse surrounding this slang reveals deep-seated anxieties about the "purity" of the national language versus the pragmatism of global fluency. This study contributes to the field of world Englishes by illustrating how language becomes a battlefield for class competition and social mobility in a rapidly globalizing Southeast Asian metropolis.